Blood Levels and Composition of Leukocyte-Platelet Aggregates in Inflammatory Diseases of Various Etiologies - Peshkova, Alina; Saliakhutdinova, Shakhnoza M; Sounbuli, Khetam; Andrianova, Izabella; Litvinov, Rustem I.; Weisel, John W (Thrombosis and Haemostasis)
Leukocyte-platelet aggregates (LPAs) play a crucial role in the pathogenesis of inflammatory diseases, linking pathological immune responses with thrombosis. The levels of LPAs, their composition, and cellular reactivity were determined in patients with distinct inflammatory conditions, namely COVID-19, rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE), compared to healthy controls. Flow cytometry was used to identify cell types and measure LPA levels in the blood. The ability of platelets, neutrophils, and monocytes to form additional LPAs in response to hyper-stimulation with phorbol-12-myristate-13-acetate (PMA) was assessed. Co-aggregation of isolated neutrophils and platelets in vitro was visualized using scanning electron microscopy. Blood tests included coagulation, hematology, biochemistry, and immunology. LPA levels were significantly higher in all patient groups compared to controls, with variations in the composition: neutrophil-platelet aggregates predominated in the COVID-19 patients, while monocyte-platelet aggregates prevailed in the blood of RA and SLE patients. Platelet-to-leukocyte ratios within aggregates varied in a broad range with a substantial prevalence of platelets over leukocytes. Morphological analysis revealed co-aggregation of platelets with neutrophils, including relatively large homotypic platelet aggregates associated with one or two neutrophils. In PMA-treated pathological blood samples from COVID-19, RA, and SLE patients, the ability to form additional LPAs over the patients’ baseline level was reduced compared to normal blood samples, indicating impaired reactivity (exhaustion) of neutrophils and monocytes in all patient groups. This study highlights distinct changes in the number and composition of LPAs in inflammatory diseases of various etiologies associated with altered functionality of the innate immune cells.